2022
DOI: 10.1063/5.0085961
|View full text |Cite
|
Sign up to set email alerts
|

Formation of tungsten carbide by focused ion beam process: A route to high magnetic field resilient patterned superconducting nanostructures

Abstract: A scale for magnetic field resilience of a superconductor is set by the paramagnetic limit. Comparing the condensation energy of the Bardeen–Cooper–Schrieffer (BCS) singlet ground state with the paramagnetically polarized state suggests that for an applied field [Formula: see text] (in SI), singlet pairing is not energetically favorable. Materials exceeding or approaching this limit are interesting from fundamental and technological perspectives. This may be a potential indicator of triplet superconductivity, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The value of T c , however, presents a non-monotonic dependence with the current, first increasing with increasing current, up to a significant figure of 6.2 K at 50 pA, and then decreasing again when the ion beam current is further increased. Whereas W-C deposits were first described within s-wave type-II superconductivity [73] some authors have recently reported anisotropic superconductivity features [74].…”
Section: Tungstenmentioning
confidence: 99%
“…The value of T c , however, presents a non-monotonic dependence with the current, first increasing with increasing current, up to a significant figure of 6.2 K at 50 pA, and then decreasing again when the ion beam current is further increased. Whereas W-C deposits were first described within s-wave type-II superconductivity [73] some authors have recently reported anisotropic superconductivity features [74].…”
Section: Tungstenmentioning
confidence: 99%
“…Since the sputtering rate not only depends on the mass but also on the bond strength, preferential sputtering of light atoms could be (partially) suppressed if strong chemical bonds are formed. Deposits derived from W(CO)6 by Ga + -FIBID for example, have a very low (0 at% 135,202 to 8 at% 203 ) oxygen content while the C:W ratio is close to one. This indicates the effective formation of tungsten carbide, which was also confirmed by atom probe tomography showing only signals corresponding to WC while no atomic tungsten ions were observed.…”
Section: Co2(co)8mentioning
confidence: 99%
“…This indicates the effective formation of tungsten carbide, which was also confirmed by atom probe tomography showing only signals corresponding to WC while no atomic tungsten ions were observed. 135 A potential explanation is that carbon will be bound strongly to tungsten, drastically reducing its sputtering rate while oxygen is still removed preferentially due to its lower mass. A similar trend is observed in the case of Mo(CO)6.…”
Section: Co2(co)8mentioning
confidence: 99%